Comparative reproductive biology of Sciaenidae family species in the Rı´o de la Plata and Buenos Aires Coastal Zone, Argentina - Militelli, Maria Ines (2013)
A comparative analysis on various aspects of the reproductive biology of 7 Sciaenidae family species was done. In addition the reproductive parameters needed for stock assessment models were provided. The research covered the analysis of the duration of the breeding season and the estimation of reproductive variables such as size at maturity, fecundity and spawning frequency. When all species were considered together, some aspects of reproduction were similar, regarding the reproductive strategy; all species are batch spawners with indeterminate fecundity and an extensive reproductive season (approximately six months) except for Pogonias cromis, which showed a more limited spawning season (three months). With regard to reproductive potential, wide differences in fecundity values mainly due to the different sizes attained by each species were observed (range in batch fecundity values between 5000 and 2,800,000 hydrated oocytes). However, when relative fecundity was compared, average values were generally similar, ranging approximately between 150 and 200 hydrated oocytes per female gram. Pogonias cromis is the exception within this group, because the mean relative fecundity ranged between 75 and 98 hydrated oocytes per ovary-free female gram. This difference may be a consequence of the greater oocyte size reached by P. cromis eggs (1100 –1400 mm) compared to the rest of sciaenid analysed (750 –900).